Исследование взрывобезопасности полимерных ограничителей перенапряжений 3,3 кВ постоянного тока для тяговой сети железнодорожного транспорта - Шумилов, Ю.Н.; Бондаренко, В.И. (Електротехніка і електромеханіка, 2019)
Проведены испытания полимерных образцов ОПН-3,3 кВ в эксплуатационных условиях на оборудовании действующей подстанции, при токах короткого замыкания 8,3 кА и времени воздействия тока 0,02 с, близких по величине к рекомендуемым стандартом IEC 60099-4:2014 значениям. Испытано 8 шт. ограничителей перенапряжений. In the testing laboratories of Ukraine, there is no high-voltage equipment of the necessary energy for testing surge arresters for explosion safety, which does not allow to estimate this indicator at the stage of development of prototypes. In view of this test, the polymer prototypes of the DC surge arresters in polymer case (SAp) 3.3 kV were tested under the operating conditions of the equipment of the operating substation with short-circuit currents of 8.3 kA and a current time of 0.02 seconds, close to the recommended by Standard of IEC 60099-4:2014 values.